PENGGUNAAN AIR KELAPA DAN ASPIRIN UNTUK PRESERVASI UBI JALAR (IPOMEA BATATAS) SECARA IN VITRO - Yelli, Fitri (JURNAL AGROTROPIKA, 2020)
Sweet potato is raw locally food used as an alternative staple food that important for national food security. The objective of the reseach was to achive the suitable medium for preservation of sweet potato plants by slowly growth in in vitro medium. The factorial experiment arranged in completely randomized design with the first factor was two concentrations of MS medium: MS 1 and MS 2. The second factor was several concentrations of coconut water, i.e. 0 and 15 mg/l and the third factor was several concentrations of Aspirin (0, 5, 10, 15, 20 mg/l) . The results showed that the number of green leaves and the number of internodes were affected by concentrations of medium in six weeks after planting. The MS1 medium with 0 mg/l Aspirin and 15 mg/ coconut water could produced the higher number of green leaves (8,0) and 8,5 internodes number. The MS2 + 15 mg/l coconut water and 15 mg/l Aspirin was the best medium for sweet potato preservation. Data obtained also showed that all medium containing Aspirin produced the high number of root. Keywords : Sweet potato, coconut water, Aspirin, preservation, in vitro.